IMPROVING VOCABULARY MASTERY OF TENTH GRADE STUDENTS THROUGH “BROAD RACES” GAME IN SMK YPKKP CIJERAH BANDUNG - Widianingsih, Wiwin; Jubaedah, Dida; Syatroh, Isry Laila (IKIP Siliwangi, 2020)
This research is aimed at increasing the mastery of English vocabulary at tenth grade in SMK YPKKP Cijerah Bandung. The technique used is the “Broad Races” game. The data were obtained from tests. The low mastery of English vocabulary at tenth grade SMK YPKPP Cijerah Bandung is caused by two factors : 1) low level of understanding of English vocabulary meaning, and 2) students’ difficulty in pronouncing the words. The method used in this research is classroom action research using two cycles. In each cycle there were five meetings. The total meetings were ten meetings; three meetings were for tests, and seven meetings were for treatments. The test result showed that “Broad Races” game is able to improve students’ vocabulary, and facilitate students in memorizing vocabulary. The students’ mean scores have improved. The mean score of pre-test was 4.8, while the mean score of post-test was 7,6. Before the treatment in cycle 1, 8 of 30 students (26%) got the scores above the passing grade (Kriteria Ketuntasan Minimal-KKM). While after the treatment in cycle 1, 22 out of 30 students (73%) got the above passing grade (Kriteria Ketuntasan Minimal-KKM). Therefore, it can be suggested that “Broad Races” game can be an alternative way to teach English vocabulary. This result hopefully can give contribution to English teachers to use “Broad Races” game in improving students’ English vocabulary mastery. Keywords: Broad Races, CAR, English Vocabulary